How to manage patellofemoral pain – Understanding the multifactorial nature and treatment options - Lack, Simon; Neal, Bradley; De Oliveira Silva, Danilo [UNESP]; Barton, Christian (Elsevier, 2018)
Patellofemoral pain (PFP) is one of the most prevalent conditions within sports medicine, orthopaedic and general practice settings. Long-term treatment outcomes are poor, with estimates that more than 50% of people with the condition will report symptoms beyond 5 years following diagnosis. Additionally, emerging evidence indicates that PFP may be on a continuum with patellofemoral osteoarthritis. Consensus of world leading clinicians and academics highlights the potential benefit of delivering tailored interventions, specific to an individual's needs, to improve patient outcome. This clinical masterclass aims to develop the reader's understanding of PFP aetiology, inform clinical assessment and increase knowledge regarding individually tailored treatment approaches. It offers practical application guidance, and additional resources, that can positively impact clinical practice.
Keywords: Biomechanics; Education; Patellofemoral pain; Rehabilitation